Little Miss Scary - Hargreaves, Roger 1935-1988; Hargreaves, Roger 1935-1988; Chorion (Firm) (London Egmont, 2003)
Little Miss Scary loves to scare the socks off of the other Mr. Men and Little Misses. But can she handle it when the tables are turned?
Keywords: Etiquette -- Juvenile fiction; Picture books; Etiquette; Picture books; Fiction; Juvenile works